Father-child attachment in adoptive gay father families. Issue 1 (2nd January 2020) - McConnachie, Anja L.; Ayed, Nadia; Jadva, Vasanti; Lamb, Michael; Tasker, Fiona; Golombok, Susan
ABSTRACT: The attachment security of children in 30 gay father families, 29 lesbian mother families and 38 heterosexual parent families was investigated using the Friends and Family Interview (FFI) at the second phase of a longitudinal study. Children in gay father families showed significantly higher levels of secure-autonomous attachment than children in heterosexual parent families, significantly lower levels of preoccupied attachment than children in either lesbian mother or heterosexual parent families, and significantly lower levels of disorganised attachment than children in heterosexual parent families. For children in gay father families, stepwise multiple regression revealed that neither hyperactivity nor emotional symptoms at Phase 1 were predictive of disorganisation at Phase 2. However, when entered alone, Phase 1 emotional symptoms predicted Phase 2 disorganisation. The results indicate that adopted children in gay father families are at least as likely to be securely attached as children in lesbian mother or heterosexual parent families.